Optimising the combination of thermostabilising mutations in the neurotensin receptor for structure determination - Shibata, Yoko (2013)
Conformational thermostabilization of G protein-coupled receptors is a successful approach for their structure determination. We have recently determined the structure of a thermostabilized neurotensin receptor NTS1 in complex with its peptide agonist and here we describe the strategy for the identification and combination of the 6 thermostabilising mutations essential for crystallisation. First, thermostability assays were performed on a panel of 340 detergent-solubilised Ala/Leu NTS1 mutants and the best 16 thermostabilizing mutations were identified. These mutations were combined pair-wise in nearly all combinations (119 out of a possible 120 combinations) and each mutant was expressed and its thermostability experimentally determined. A theoretical stability score was calculated from the sum of the stabilities measured for each double mutant and applied to develop 24 triple mutants, which in turn led to the construction of 14 quadruple mutants. Use of the thermostability data for the double mutants to predict further mutant combinations resulted in a greater percentage of the triple and quadruple mutants showing improved thermostability than if only the thermostability data for the single mutations was considered. The best quadruple mutant (NTS1-Nag36k) was further improved by including an additional 2 mutations (resulting in NTS1-GW5) that were identified from a complete Ala/Leu scan of Nag36k by testing the thermostability of the mutants in situ in whole bacteria. NTS1-GW5 had excellent stability in short chain detergents and could be readily purified as a homogenous sample that ultimately allowed crystallisation and structure determination.